Fabrication and characterisation of CuO nanotubes electrodeposited into aluminium oxide template in ionic liquid. (April 2014) - Liang, Z.; Xie, X.; Jia, J.; Lu, P.; Zhong, L.; Han, L.; Fan, C.
Abstract : CuO nanotubes are fabricated by direct current electrodeposition within the porous anodic aluminium oxide (AAO) template in urea–NaBr–KBr–CuCl2 –acetamide ionic liquid. The AAO membrane is subject to the dual oxidation (two-step) anodising. The composition and morphology of the as prepared products are characterised using X-ray diffraction pattern and scanning electron microscopy images. Results indicate that the CuO nanotubes with 3–4 μm length and 80 nm diameter grow, which is perpendicular to the substrate. The results provide a new method for the synthesis of nanotubes.